Spatiotemporal dynamics evaluation of pixel-level gross domestic product, electric power consumption, and carbon emissions in countries along the belt and road - Zhong, Liang; Liu, Xiaosheng; Ao, Jianfeng (Energy (Oxford), 2022)
The ambiguous relationship between the international economy, energy, and carbon emissions has become a significant factor restricting sustainable development. This study attempts to reveal the spatiotemporal dynamics and interrelationships of gross domestic product (GDP), electric power consumption (EPC), and carbon emissions (CE) in the Belt and Road (B&R) regions using Suomi National Polar-orbiting Partnership (NPP) Visible Infrared Imaging Radiometer Suite (VIIRS) remote sensing data. Annual nighttime light (ANL) images were synthesized, and the accuracy of the ANL data was improved using the multiperiod mask denoising method. Then, the GDP, EPC, and CE at 0.5 km resolution were modelled. Finally, the spatiotemporal dynamics of regional development were comprehensively analysed at multiple scales. The results reveal that the development in the eastern and western parts of the B&R regions has significant differences. China, India, and some countries in Southeast Asia have developed rapidly and in a relatively balanced manner, whereas the development of Central and Eastern Europe and western Russia has been relatively slow and uncoordinated. The geographical centre of the overall development of the B&R continued to migrate to the southeast. This study provides more detailed and comprehensive insights into GDP, EPC, and CE in the B&R regions. •Economy, energy, and carbon emissions at 0.5 km resolution were evaluated.•The spatiotemporal dynamics of regional development were analysed at multiple scales.•The development status of the east and the west showed significant differences.•Policy implications for promoting sustainable development were suggested.